Exploring the West African forest island phenomenon: scientific insights gained, successes achieved and capacities strengthened - Logah, V.; Azeez, J.; Compaore, H.; Mesele, S.A.; Ocansey, C.M.; Bougma, A.; Tetteh, E.N.; Veenendaal, E.M.; Lloyd, J. (2024)
Anthropogenic activities around local villages in mesic savanna landscapes of West Africa have resulted in soil improvement and forest establishment outside their climatic zones. Such unique ‘forest islands’ have been reported to provide ecosystem services including biodiversity conservation. However, the science underpinning their formations is limitedly studied. In 2015 and with funding support from the Royal Society-DFID (now FCDO), we set out to investigate the biogeochemistry of the forest islands in comparison with adjacent natural savanna and farmlands across 11 locations in Burkina Faso, Ghana and Nigeria. Our results showed that the forest islands do not differ significantly from the adjoining ecosystems in soil mineralogy implying that their formation was anthropogenically driven. We observed greater soil organic carbon and nutrient distributions in the forest islands, which also had more stable macro (>500 μm) and meso-aggregates (500–250 μm) than the adjoining agricultural lands. We found that soil micro-aggregate (250–53 μm) stability was climate (precipitation) driven in the West African ecosystems while meso- and macro-aggregate stability was land-use driven. In one of the unique forest islands we studied in the Mole National Park of Ghana, we found its mineral-associated organic carbon over 40% greater than the adjoining natural savanna with potential implications for the achievement of the global initiative of the ‘4p1000’ in West Africa. We conclude that the North–South–South research collaboration has established clearly, the science underlying the age-long West African forest island phenomenon and has, among many successes, led to capacity building of young scientists driving cutting-edge research in climate change adaptation and food systems transformation in the sub-region.